The Effect Of Content Differentiation Learning Strategy On The Narrative Text Writing Ability Of 4th Grade Students At Bangsalsari 05 Elementary School - Putri, Safina Aulia; Muti'ah, Arju; Yuliati, Nanik; Wuryaningrum, Rushianti; Naim, Mohammad (PT. Hafasy Dwi Nawasena, 2025)
Differentiated learning strategies are designed to meet the diverse needs of students by varying content, process, product, or learning environment, and by providing materials tailored to students' learning styles, such as PowerPoint for visual learners, instructional videos for audiovisual learners, and role-playing activities for kinesthetic learners, which enhances motivation and comprehension. This study, using a quantitative method with a quasi-experimental design (matching pretest-posttest control group design), aims to explore the impact of content differentiation strategies on narrative writing skills of Grade IV students at SDN Bangsalsari 05. Involving 20 students from Class IVA as the experimental group and 20 students from Class IVB as the control group, the results showed that the pretest scores for the control group ranged from 46 to 63 with an average of 52.7, and the experimental group had scores from 46 to 66 with an average of 55.75. Posttest results showed an improvement in both groups, with the control group scoring between 53 and 85 (average 69.35) and the experimental group between 70 and 98 (average 83.8). The t-test result of -5.063 compared to the t-table value of 1.725, with a significance value of 0.000 < 0.05, indicates a significant impact of the content differentiation strategy on improving the narrative writing skills of the students.